f = {(1, 1),(0, -3)}
g = {(1, 0), (-3, 1), (2, 1)}
This tells us that
f(1) = 1
f(0) = -3
g(1) = 0
g(-3) = 1
g(2) = 1
Therefore, we want to find: fog(1), fog(-3), fog(2)
(fog)(1) = f(g(1)) = f(0) = -3
(fog)(-3) = f(g(-3)) = f(1) = 1
(fog)(2) = f(g(2)) = f(1) = 1
We also want to find gof(1), gof(0)
gof(1) = g(f(1)) = g(1) = 0
gof(0) = g(f(0)) = g(-3) = 1
2007-01-09 19:49:26
·
answer #1
·
answered by Puggy 7
·
1⤊
0⤋
Here
f = {(1, 1),(0, -3)}
g = {(1, 0), (-3, 1), (2, 1)}
This means
f(1) = 1, f(0) = -3 and g(1) = 0, g(-3) = 1, g(2) = 1
Now,
Find the value of gof(1), gof(0)
gof (1) = g(f(1)) = g(1) = 0
gof (0) = g(f(0)) = g(-3) = 1
Also
Find the value of fog(1), fog(-3), fog(2)
fog (1) = f(g(1)) = f(0) = -3
fog (-3) = f(g(-3)) = f(1) = 1
fog (2) = f(g(2)) = f(1) = 1
2007-01-09 20:17:30
·
answer #2
·
answered by Kinu Sharma 2
·
0⤊
0⤋
f = {(1,1), (0,-3)}
g = {(1,0), (-3,1), (2,1)}
For fog we need to apply f to every element of g:
fog = {(1, f(0)), (-3, f(1)), (-2, f(1))}
= {(1, -3), (-3, 1), (-2, 1)}
Similarly we get
gof = {(1, g(1)), (0, g(-3))}
= {(1, 0), (0, 1)}
2007-01-09 19:42:23
·
answer #3
·
answered by Scarlet Manuka 7
·
0⤊
0⤋
f = {(0,0), (4, -2)}
g = {(0,4), (-2,0), (5,0)}
2017-02-06 00:55:14
·
answer #4
·
answered by jenny 1
·
0⤊
0⤋
They will not exist as g is not a function
2007-01-09 22:08:11
·
answer #5
·
answered by sidd the devil 2
·
0⤊
1⤋
Go with Puggy, not Scarlet Manuka. I assure you, Puggy's answer is perfect. (No, he's not my pal -- I don't know him).
2007-01-09 19:59:56
·
answer #6
·
answered by Hy 7
·
0⤊
0⤋